Techniques application on cultural and artistic documentary production: a study of Simon Schama’s Power of the Art - Yi, Ye Jing; Mohd Helmi Abd Rahim,; Shahrul Nazmi Sannusi, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The study objects of this research is Simon Schama’s Power of the Art, a documentary with 8 sets and of length 430 minutes. This research explores the documentary through content analysis. The study analyzes artistic expressions like theme, audio-visual language, montage technique, space-time structure, and so on. The purpose is to study how BBC creators reappear and restore history and explain artistic work through video language. How they use artistic and aesthetic expressions with ideological implications in showing and leading the viewers to think. This excellent documentary owns great reference which is significant for future creation of documentaries of similar state.